2013
DOI: 10.1111/j.1521-0391.2013.12088.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis withdrawal in chronic, frequent cannabis smokers during sustained abstinence within a closed residential environment

Abstract: Objectives: Chronic, frequent cannabis smokers may experience residual and offset effects, withdrawal, and craving when abstaining from the drug. We characterized the prevalence, duration, and intensity of these effects in chronic frequent cannabis smokers during abstinence on a closed research unit. Methods: Non-treatment-seeking participants (N ¼ 29 on admission, 66% and 34% remaining after 2 and 4 weeks) provided subjective effects data. A battery of five instruments was computer-administered daily to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 33 publications
9
21
3
Order By: Relevance
“…It revealed a gender effect on CWS-severity and related CWS-severity to CGI-S, thus making the intensity of CWS comparable to other disorders. Negative correlations between CWS-severity and serum levels of THC and, more robustly, of THC-OH and THC-COOH were found at baseline, which extended recently published results that described a negative relationship between serum THC and two single withdrawal symptoms ('difficulty getting off to sleeping' and 'anxious') (Lee et al, 2014). Among the single withdrawal symptoms in our study, only for 'strange dreams' a significant correlation with serum THC was found.…”
Section: What Is New About This Study?supporting
confidence: 90%
See 4 more Smart Citations
“…It revealed a gender effect on CWS-severity and related CWS-severity to CGI-S, thus making the intensity of CWS comparable to other disorders. Negative correlations between CWS-severity and serum levels of THC and, more robustly, of THC-OH and THC-COOH were found at baseline, which extended recently published results that described a negative relationship between serum THC and two single withdrawal symptoms ('difficulty getting off to sleeping' and 'anxious') (Lee et al, 2014). Among the single withdrawal symptoms in our study, only for 'strange dreams' a significant correlation with serum THC was found.…”
Section: What Is New About This Study?supporting
confidence: 90%
“…Their cannabis consumption was in the upper range compared with other clinical studies on CWS (Budney et al, 2004;Arendt et al, 2007;Levin et al, 2010;Allsop et al, 2011;Lee et al, 2014). In contrast to other prospective studies (Budney et al, 1999(Budney et al, , 2004Arendt et al, 2007;Preuss et al, 2010;Lee et al, 2014), all patients developed a CWS in our study. …”
Section: Samplecontrasting
confidence: 78%
See 3 more Smart Citations